PERANAN KOMUNIKASI INTERPERSONAL DALAM MENYELESAIKAN KONFLIK PADA HUBUNGAN PERSAHABATAN REMAJA - Abednego Edy Suranta Tarigan, Muhammad Alfikri (PERSPEKTIF, 2013)
The research aim is to explore friendship among teenagers. Interesting about friendship is because conflict is often happened and friendship is getting decline. The conflict began when negotiation process was failed. Then, their communication process will change. Researcher wants to explore what makes conflict among teenagers and the solutions. This research is quantitative descriptive. Research site is in Kartika I-II High School Medan, with consideration of pre-survey questionnaire result of research. 64% respondents have conflict with their friends.